Penerapan Prinsip Tanggung Jawab Renteng (Joint Liability) dalam Perlindungan Hak Normatif Bagi Pekerja Outsourcing - Kadek Yogi Arya Agustama (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
This research examines the urgency of implementing the principle of joint liability in outsourcing labor relations in Indonesia following the enactment of Law Number 6 of 2023 concerning Job Creation. The primary issue addressed is the imbalance in the protection of workers' normative rights when service providers default, while user companies tend to distance themselves from legal responsibility due to the absence of a direct contractual employment relationship. The research methodology employed is juridical normative, utilizing a statutory approach and a conceptual approach. The results indicate that the flexibility of the outsourcing system in recent regulations often overlooks aspects of job security and worker welfare. The application of the joint liability principle is viewed as a fair legal solution to ensure that fundamental worker rights, such as minimum wages, social security, and compensation, remain fulfilled despite financial constraints on the service provider's side. The integration of responsibility between provider and user companies not only provides a guarantee for the workforce but also encourages the creation of a more ethical and responsible business climate. The research conclusion emphasizes that to achieve a balance between business efficiency and labor protection, national regulations need to clarify the position of collective responsibility in outsourcing practices in Indonesia.